WHO Expert Committee on Biological Standardization : sixtieth report (Technical report series (World Health Organization), 2013)
This report presents the recommendations of a WHO Expert Committee commissioned to coordinate activities leading to the adoption of international recommendations for the production and control of vaccines and other biologicals and the establishment of international biological reference materials. The report starts with a discussion of general issues brought to the attention of the Committee and provides information on the status and development of reference materials for various antibodies antigens blood products and related substances cytokines growth factors endocrinological substances and i.